LOKAKARYA PEMBERDAYAAN KEARIFAN LOKAL DALAM KEGIATAN BELAJAR MENGAJAR BAGI GURU SEKOLAH DASAR GUGUS OENAMO B KABUPATEN TTU - Cornelia Amanda Naitili; Yulsy Marselina Nitte; Vera Rosalina Bulu; Asti Yunita Benu; Viki Vikranta Yorhans Dollok (Pengabdian Masyarakat Ilmu Pendidikan, 2023)
One form of independent curriculum implementation is the Pancasila learner profile, which is developed by integrating local wisdom in learning. However, the reality is that there is still a lack of empowerment of local wisdom in teaching and learning activities by teachers in primary schools in Gugus Oenamo B. Therefore, this workshop aims to improve teachers' competence in recognizing, appreciating, and utilizing local wisdom in the teaching and learning process. The workshop was conducted offline in SD Negeri Unina, Biboki Moenleu sub-district, TTU district. The workshop participants were the headmaster and teachers of SD Gugus Oenamo B. The workshop was successful in providing teachers with the understanding and skills to utilize local wisdom in teaching and learning activities, especially in the production of learning media.